Accountability for development cooperation under the 2030 Agenda - Timo C. Mahn (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
What is the contribution of development cooperation to the 2030 Agenda, and how can accountability for that contribution be ensured? Implementing the 2030 Agenda will require a move from “Billions to Trillions”. However, the operationalization of commitments relies heavily on the traditional concept such as Official Development Assistance (ODA). In the future development cooperation will have to shift focus on leaving no one behind, providing seed funding and catalytic support, as well as leveraging additional resources. Strengthening the accountability of all contributions and maximizing their impact will be key, necessitating adjustments to principles and arrangements for (mutual) accountability. Towards Collective Accountability The operational value of “Mutual accountability” has been limited so far given power imbalances, unclear roles and objectives, lack of enforceability and overlapping accountability strands. Future collective Accountability will have to encompass not just public, but also private and civil society actors. Such collective accountability mechanisms can no longer enforce, but only incentivize action through peer-pressure, penalizing inertia through reputational damage, and encourage dialogue and reciprocal learning. Given the broad scope of the 2030 Agenda, achieving priorities and assigning responsibilities are clear obstacles. For development cooperation, the aid/development agenda may have continued value in that regard. Interlinkages between existing accountability frameworks and the 2030 Agenda In order for the United Nations High Level Political Forum (HLPF) to emerge as the locus of “global accountability”, the entry points, channels and feedback loops for the inputs from various stakeholders require further specification. Synergies and complementarities of existing accountability mechanisms for development cooperation need to be further exploited. Established frameworks such as the GPEDC, DCF and DAC lack stronger horizontal linkages to “global accountability” under the 2030 Agenda. There are also gaps in the vertical linkages between national, regional and global layers in both the development cooperation policy field, and for the 2030 Agenda. The principle of “subsidiarity” might be useful in organizing responsibilities. Development cooperation Stakeholders should better align their roles, activities and commitments with the 2030 accountability framework, including by sequencing meeting calendars, coordinating inputs, and aligning the timing and content of monitoring surveys.
Keywords: 330; Agenda 2030